Mobile games on the basis of uses and gratifications approach: A comparison of the mobile game habits of university and high school students. (December 2019) - Bulduklu, Yasin
The aim of this study was to determine the attitudes of university and high school students towards mobile games, and to investigate their motivation and gratification needs in terms of mobile gaming. The descriptive method was used in the study. The sampling group was composed of 846 participants. The data were collected through the Mobile Gaming Motivation Survey. The reliability coefficient of the survey (Cronbach's alpha) was found to be 0.893. The data analysis revealed that the mobile gaming motives of participants were self-realization/individual gratification, rivalry, social interaction, addiction and escaping. It was concluded that the motivation of the participants to play mobile games and the time they spent on mobile gaming decreased as their education level increased. It was also found that the mean scores for each factor got lower as the age progressed.